تأثير الضغط المؤسساتي على الأهمية المدركة لتبني المحاسبة الإدارية البيئية "دراسة تجريبية على بعض الشركات الصناعية" - الأمين ماهر; داود ساميا أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى التحقق من العلاقة بين الضغط المؤسساتي (القسري، المعياري، التقليد) والأهمية المدركة لتبني ممارسات المحاسبة الإدارية البيئية استناداً إلى النظرية المؤسساتية. وبشكل أكثر تحديداً معرفة العلاقة بين ضغط الحكومة والمنظمات المهنية والمنظمات الأخرى في المجتمع على الأهمية المدركة لتبني ممارسات المحاسبة الإدارية البيئية. وقد تم بناء الفروض على أن هناك علاقة طردية بين الضغط المؤسساتي (المماثلة القسرية، الضغط المعياري، عمليات التقليد) والأهمية المدركة لتبني ممارسات المحاسبة الإدارية البيئية. وتم جمع المعلومات لاختبار هذه الفروض عن طريق توزيع استبيان على 63 مديرا من مدراء الأقسام العاملين في 20 شركة صناعية سورية. وقد أظهرت النتائج وجود علاقة طردية بين المماثلة القسرية والضغط المعياري والأهمية المدركة لتبني ممارسات المحاسبة الإدارية البيئية. ولم توجد أية علاقة بين عمليات التقليد والأهمية المدركة لتبني ممارسات المحاسبة الإدارية البيئية. وقد تم مناقشة هذه النتائج وتقديم التوصيات بناء على هذه النتائج. This research examines the impact of institutional pressure on perceived importance of the environmental management accounting (EMA) adoption. Specifically, it looks at the pressure of government and other parties in society concerning EMA adoption among manufacturing companies in Syria. Drawing on the institutional theory, the research seeks to identify the extent to which institutional pressure influences perceived importance of EMA adoption. Hypotheses that were constructed have assumed a positive relationship between the Institutional pressure (coercive isomorphism, normative pressure and mimetic processes) and the perceived importance of the (EMA) adoption. A total of 63 managers working in 20 Syrian manufacturing companies participated in the survey. Institutional pressure (coercive isomorphism, normative pressure and mimetic processes) was tested against the perceived importance of the (EMA) adoption via simple regression analysis and correlation. The findings revealed that there is a positive relationship between the coercive isomorphism and normative pressure and the perceived importance of the (EMA) adoption. In addition, there is no relationship between the mimetic processes and the perceived importance of the (EMA) adoption. The findings have been discussed and some recommendations and suggestions have been provided.